A 34‐Electron Superatom Ag78 Cluster with Regioselective Ternary Ligands Shells and Its 2D Rhombic Superlattice Assembly. Issue 8 (29th December 2020) - Zhang, Wen‐Jing; Liu, Zhen; Song, Ke‐Peng; Aikens, Christine M.; Zhang, Shan‐Shan; Wang, Zhi; Tung, Chen‐Ho; Sun, Di
Abstract: Herein, we report a 78‐nuclei silver nanocluster (NC) [Ag78 ( i PrPhS)30 (dppm)10 Cl10 ] 4+ (SD/Ag78a ; dppm=bis‐(diphenylphosphino)methane) that was synthesized through a one‐pot reaction using [Ag(pz)] n as precursor (Hpz=pyrazole) and further characterized by X‐ray crystallography. SD/Ag78a shows a core–shell structure comprised of an all‐metallic Ag53 kernel surrounded by an Ag25 discontinuous metal–organic shell. The Ag53 kernel is an Ag13 Ino decahedron encaged by an Ag40 drum‐like shell, while the Ag25 shell consists of two Ag10 S10 P10 Cl5 rings and five S‐Ag‐S staples. Three types of ligands regioselectively cap on the surface of the Ag78 NC, forming diverse metal–ligand interfacial structures. The NC is a closed‐shell 34‐electron superatom with +4 charge state and shows highly featured molecule‐like absorption spectra in the UV/Vis region with a maximum around 493 nm. The rhombic superlattice assembled from SD/Ag78a through intercluster C−H⋅⋅⋅π interactions can be formed by a simple drop‐casting treatment. Abstract : SD/Ag78a shows a core–shell structure comprised of an all‐metallic Ag53 kernel surrounded by an Ag25 discontinuous metal–organic shell. Thiolate, phosphine, and chloride ligands are shown to regioselectively ligate on the surface of the Ag78 nanocluster.